Differential expression of lncRNA/miRNA/mRNA and their related functional networks during the osteogenic/odontogenic differentiation of dental pulp stem cells. Issue 4 (24th September 2019) - Liu, Zhongjun; Xu, Shuaimei; Dao, Junfeng; Gan, Zekun; Zeng, Xiongqun
Abstract: Dentin‐pulp regeneration requires dental pulp stem cells (DPSCs), but the role of long noncoding RNAs (lncRNAs) during this process remains unclear. Here, we cultured human DPSCs in osteogenic/odontogenic medium for 14 days and analyzed cells via RNA‐sequencing. The data were validated by quantitative reverse transcription‐polymerase chain reaction and lncRNA–microRNA (miRNA)–messenger RNA (mRNA) networks were constructed to reveal the potential competing endogenous RNA regulatory role of lncRNAs. Kyoto Encyclopedia of Genes and Genomes and Gene Ontology enrichment analysis were performed. One lncRNA, SNHG7, was identified and validated by genetic shRNA silencing. A total of 89 lncRNAs, 1, 636 mRNAs, and 113 miRNAs were differentially expressed after differentiation. Bioinformatics identified an array of affected signaling pathways including phosphoinositide‐3‐kinase–protein kinase B, transforming growth factor‐β, and Wnt. mRNAs were enriched in cell migration, cell differentiation, stem cell development, ossification, and skeletal development. One lncRNA, SNHG7, was indentified to inhibit the odonto/osteogenic differentiation of DPSCs when silenced. In summary, we reveal several lncRNAs that significantly change during DPSC differentiation, including SNHG7. This reveals new targets for dentin‐pulp complex regeneration and tissue engineering. Abstract : We indentified differentially expressed lncRNAs/miRNAs/mRNAs during dental pulp stem cell odonto/osteoblast differentiation, including SNHG7. This reveals new targets for dentin‐pulp complex regeneration and tissue engineering.